Intention to Purchase Halal Cosmetic Products in an Islamic Pakistani Culture - Zahid Hussain (Journal of Islamic Economics and Finance Studies, 2022)
The purpose of this study is to determine the impact of Muslim customers' purchases of halal cosmetic products in Pakistan. Multiple linear regressions were used in this study. The data was collected from 223 Muslims who were all over the age of 18. Product quality, religious belief, halal awareness, personal societal perception, and halal certification were five of the six hypotheses tested. Results were found to have a significant impact on customer intentions to buy halal cosmetic products in Pakistan. According to the findings, customers' intentions to purchase halal cosmetics are influenced by brand perception. According to the findings of this study, halal certification is the most important factor influencing customer intentions to buy halal cosmetics.